PAYUDARA SENDIRI (SADARI) SEBAGAI DETEKSI DINI KANKER PAYUDARA TERHADAP TINGKAT PENGETAHUAN REMAJA PUTRI DI SMA SWASTA GKPI MEDAN - Sri Muryana Simamora; Harsudianto Silaen (Jurnal Riset Multidisiplin Edukasi, 2025)
The most common early detection method for breast cancer is breast self-examination (BSE). BSE is very simple and can be performed by all women without feeling embarrassed by the examiner. BSE can be performed on women starting from the age of 20 years and above or more than 7-10 days after menstruation. However, with the progress of the world, BSE can also be performed from the age of 13-20 years and can be done routinely for the prevention and early detection of breast cancer. BSE can be done every month during the menstrual cycle as an early detection of breast cancer. Objective: To analyze the effect of health education about breast self-examination (BSE) as an early detection of breast cancer on increasing the knowledge of young women in GKPI Medan private high schools. Method: This study uses a quantitative method with a pre-experimental research design and uses a one-group pre-post test design approach. Sampling using a total sampling technique totaling 110 respondents. Research data analysis uses the Wilcoxon sign rank test. Results: Based on the Wilxocon test, the results of this study show a significant effect of health education on BSE on the level of knowledge of female students with a p-value of 0.00 <0.05. Conclusion: There is a significant effect of Health Education on Breast Self-Examination (BSE) as an Early Detection of Breast Cancer on Increasing the Knowledge of Young Women in Gkpi Private High Schools in Medan in 2024. Suggestion: For further research, it is hoped that further research will be carried out by adding other variables such as the attitudes of female students in detecting their own breasts.